Role of Recombinant Activated FVII in Severe Post‐Partum Haemorrhage - Fatima Khanum, Muniza Qayyum, Amna Khanum, Zohra Khanum (Pakistan Journal of Medical & Health Sciences, 2023)
In Pakistan, improvement of health care structure and evolution of perinatal care, have led to momentous drop in pregnancy related deaths, however obstetrical haemorrhage maintains to be the principal cause of maternal motility. The aim of this study was to probe the utilization of activated, and recombinant, Factor VII (rFVIIa) in cases of severe postpartum haemorrhage (PPH). This study was carried out at Unit 2 of Obstetrics & Gynaecology Department of Sir Ganga Ram Hospital (Fatima Jinnah Medical University), Lahore, over a period of 10 weeks, from 15/01/2023, to 31/03/2023. Fifteen females with severe PPH who were treated with rFVIIa were included in this study. The overall observed median and mean blood loss were 8639 mL and 11835 mL respectively. The management prior to rFVIIa involved trans-arterial embolization in five patients, while three of them had hysterectomy. One patient had one single dose, two of them had two doses, three of those patients had four doses, two patients had five plus doses, and a single patient had twenty plus doses of rFVIIa. The mean (± SD) of single dose was at 81.60 ± 16.25 µg/kg. Fourteen of those females could survive, however one of them died due to complication. The cause of that death was uterine rupture, and the quantum of haemorrhage in that case of death, was 6428–43 810 mL. This may, therefore, lead us to conclude that, irrespective of the fact whether a patient would survive or otherwise, much dependents upon her general health and proceeding rFVIIa infusion, rather than haemorrhage. Four of those females presented thromboembolic events post rFVIIa management deep vein thrombosis (DVT), DVT plus pulmonary embolism (PE), PE and acute myocardial infarction (MI). This study revealed that rFVIIa infusion had promising effects for severe PPH and markedly reduced the maternal motility. Keywords: Post-Partum Haemorrhage, Hystectomy, rFVIIa, thromboembolism